1966
DOI: 10.1128/jb.92.4.880-886.1966
|View full text |Cite
|
Sign up to set email alerts
|

Agglutinating and Precipitating Capacity of Rabbit Anti-Salmonella typhosaγG and γM Antibodies During Prolonged Immunization

Abstract: Agglutinating and precipitating capacity of rabbit anti-Salmonella typhosa yG and yM antibodies during prolonged immunization. J. Bacteriol. 92:880-886. 1966.-Antibody produced in rabbits immunized with acetone-dried typhoid bacilli was followed over a period of 445 days by agglutination and by quantitative precipitation. Repeated injections of vaccine resulted in suppression of antibody titers. Both-yG and yM antibodies were rapidly increased by booster injections after rest periods during which titers had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

1967
1967
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Although the somatic antigens of gram-negative bacilli elicit an immune response which appears to be predominantly yM, a considerable proportion of the antibody activity may be found in the yG fraction of serum (7, 22, 23, 26). The apparent distribution of antibody activity among the immunoglobulins depends to a large extent on the serological procedure used (21,25). Thus, in the present study, the greater portion of the activity of late sera (pools 4, 5, and 6) as measured by CF appeared to be in the -yG fractions, although the agglutinating and vibriocidal activities were greater in the yM fractions ( Fig.…”
Section: Discussionmentioning
confidence: 44%
“…Although the somatic antigens of gram-negative bacilli elicit an immune response which appears to be predominantly yM, a considerable proportion of the antibody activity may be found in the yG fraction of serum (7, 22, 23, 26). The apparent distribution of antibody activity among the immunoglobulins depends to a large extent on the serological procedure used (21,25). Thus, in the present study, the greater portion of the activity of late sera (pools 4, 5, and 6) as measured by CF appeared to be in the -yG fractions, although the agglutinating and vibriocidal activities were greater in the yM fractions ( Fig.…”
Section: Discussionmentioning
confidence: 44%
“…This is illustrated in Table I, where it can be seen that the agglutinating antibodies are mainly of the IgM class in contrast to the precipitating antibodies which are predominantly of the IgG class. In relation to the amount of antibody, however, it has been reported that for detectable agglutination, some 20 times more IgG than IgM antibodies appears to he needed (15,17). If these estimations are valid our results point to a similar protective effect of the 19S (IgM) and 7S (IgG) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This has been regarded as a variety of the "feedback mechanism ," in which specific 7S antibody suppresses further synthesis of 19S antibody [10]. In the immune response to the somatic antigens of salmonella, a single injection of the chrome-vaccine [1] prepared from salmonella or multiple injections with killed salmonella organisms elicits predominantly 19S antibody formation in animals, though a small amount of 7S antibody may appear later [5,6,8,9]. The production of 19S antibody appears to continue for a long time without being terminated by the presence of 7S antibody [7,8].…”
mentioning
confidence: 99%
“…In the immune response to the somatic antigens of salmonella, a single injection of the chrome-vaccine [1] prepared from salmonella or multiple injections with killed salmonella organisms elicits predominantly 19S antibody formation in animals, though a small amount of 7S antibody may appear later [5,6,8,9]. The production of 19S antibody appears to continue for a long time without being terminated by the presence of 7S antibody [7,8]. To investigate this rather peculiar pattern of antibody formation to salmonella 0 antigens, we examined whether specific antibodies, passively administered, suppressed further antibody production to these salmonella O antigens in mice.…”
mentioning
confidence: 99%